The relationship between the risks of adopting FinTech in banks and their impact on the performance - Hussein Ahmed Al-Shari; M. A. Lokhande (Cogent Business & Management)
Banks give great attention to identifying the risks of adopting FinTech and the extent of its negative impact on their business. This study aims to explore the relationship between the risks of adopting FinTech in banks and their impact on performance, where the balanced scorecard was used to measure performance. This study identifies four risks, which are the most important risks affecting FinTech in banks: systemic risks, operational risks, outsourcing risks, and cyber risks. The data was collected through a questionnaire for 263 respondents at the managerial level of bank branches in Yemen from October to December 2021. Structural equation modeling PLS-SEM and a disjoint two-stage approach were used to approve the model’s constructs. The current study proved the validity of the proposed relationship between the risks and the effect of risk variables on each other, except for the impact of outsourcing risks on cyber risks. Also, the study result is that cyber risks and operational risks of adopting FinTech have a negative impact on banks’ performance. But the outsourcing risks of the adoption of FinTech have a positive impact on banks’ performance the systemic risks do not affect banks’ performance. Therefore, this study is considered one of the rare studies that contribute to analyzing the risks of adopting FinTech in banks and its impact on performance. In addition, it gives a clear picture for decision-makers in banks to identify the dark side of FinTech adoption.